Adaptive Dynamic Power Management For Portable Devices - Kong, Lee Wai (2009)
Dynamic Power Management (DPM) is a popular system level power management strategy that selectively shut down idle electrical components to save power. It is suitable for portable system that offers power saving features like multiple CPU/MCU power states and electrical components that are able to be turn off. The DPM techniques designed determine when the manageable parts will be entering the low power mode. Thus, accurate prediction of future idle period is very important for a DPM to work effectively.